Job Dynamics in Albania : A Note Profiling Albania's Labor Market - Honorati, Maddalena; Johansson De Silva, Sara; Kupets, Olga; Berger, Sara (World Bank, Washington, DC, 2018)
This note provides a brief, updated analysis of jobs dynamics in Albania, providing insights into where constraints to improving jobs outcomes remain and opportunities for addressing such challenges. Results-based policy making requires timely information to identify problems, design potential solutions, and evaluate policy initiatives. Using the most recent data available on Albanian labor markets from the perspectives of labor demand (firms) and labor supply (individuals), this note provides some key insights into the current situation and important dynamics over time and across firms and workers with different characteristics. The note is complemented by two other reports that look at (i) skills development challenges from the demand (employer) side, and (ii) the role and effectiveness of the National Employment Service (NES) in reducing unemployment. This note and the aforementioned reports will serve as inputs to a jobs framework and action plan for the Republic of Albania. This note is divided into three additional sections. Following the introduction, the second section provides a profile of labor demand in Albania, looking primarily at job creation and job productivity. The third section presents a profile of labor supply, specifically who is working, what types of jobs they are employed in, and who is not working. The final section concludes with an overall brief summary of the analysis and questions to further guide the development of a jobs action plan.